The Impact of Islamic Financing on the Economic Development of Aden governorate (A Field Study at Saba, Al-kurimi and Tadhamon banks) - Iskander A. Sattar; Ammar Saleh; Omar Hubaishan (مجلة الدراسات الاجتماعية)
This study looked at the impact of Islamic finance on Yemeni economic development, with an emphasis on the role of Islamic banks in the Aden Governorate. Using a qualitative methodology, including a (50) individual sample survey. A questionnaire is used for data collection, which was analyzed with SPSS program.